GE_GERICHTE P/2155/2023 vom 8. April 2025 - GE Cour de justice (2025)
TENTATIVE(DROIT PÉNAL);LÉSION CORPORELLE GRAVE;LÉSION CORPORELLE SIMPLE;CAS DE RIGUEUR;RENONCIATION À UNE VOIE DE DROIT;EXPULSION(DROIT PÉNAL) | CP.122; aCP.22; aCP.123; CP.49; CP.66.ala.let2